Program DAMKAR (Pendampingan Penanganan Luka Bakar) Bagi Orang Tua yang Memiliki Anak Berkebutuhan Khusus - Usman Usman; Cau Kim Jiu; Kharisma Pratama; Yenni Lukita (Lembaga Pengembangan Kinerja Dosen, 2025)
Introduction: Children with Special Needs (CSN) often have sensory and motor limitations, which increase their risk of experiencing household accidents, including burn injuries. Parents caring for CSN frequently lack adequate knowledge and skills in initial burn management, which can potentially worsen the child's condition and impede the healing process. This DAMKAR (Burn Injury Management Assistance) Program aims to enhance the competence of CSN parents at the Special School (SLB Kinarsih), located at Jl. Husein Hamzah Gg. Bhineka No. 27A, in providing prompt and appropriate first aid for burn injuries.Methodology: This community service activity (PkM) was implemented using the Participatory Action Research (PAR) approach, which emphasizes active collaboration among the implementation team, the target partner SLB Kinarsih, and the participants (parents, teachers, and caregivers of CSN). The implementation consisted of 5 stages: Preparation and Assessment (Weeks 1 to 3), Socialization and Education (Weeks 4 to 6), Practical Training and Simulation (Weeks 7 to 9), Implementation and Monitoring (Weeks 10 to 11), and Evaluation and Reporting (Week 12). Results: A significant increase was observed in the parents' average knowledge score, rising from 59.5 to 88.89. Furthermore, more than 90% of participants were able to correctly demonstrate the techniques for burn management and dressing during the simulation. This enhancement in skills provided greater confidence to the parents in handling burn emergency situations. Conclusion: The DAMKAR Program successfully improved the knowledge and practical skills of CSN parents in initial burn management. This program is recommended to be integrated as a routine module in CSN care training to minimize the risk of complications and enhance the quality of life for the child and family.